THEORETICAL ASPECTS OF FUTURE SOCIAL WORKERS’ READINESS FOR PROFESSIONAL ACTIVITY IN HIGHER EDUCATION INSTITUTIONS - Halan, Oksana (Mountain School of Ukrainian Carpaty, 2018)
Current state of society development has been characterized by a number of negative trends associated with the aggravation of socio-economic, socio-pedagogical problems and, as a result, social and psychological disadaptation has been observed in its life. In such conditions, It is necessary to qualify social workers who can contribute to the development of the educational space, the integration of social institutions and the harmonization of people’s relationships. Consequently, the need for a new generation of social work specialists has been a priority in the educational process of higher educational institutions and has been reflected in the National Strategy for the Development of Education in Ukraine until 2021 and in the Law of Ukraine “On Education”. The success of the future social worker has been observed due to the formation of his positive motivation for personal development and value attitude to social work. Therefore, the author has analyzed the content and structure of readiness of the future specialists in social sphere for their professional activity; characterized motivational-value, informational-cognitive, organizational-activity, personal-reflexive components; conducted Questionnaires and discussions with students on the identified issues. It has been proven that the motivational-value component of the readiness of future social workers for professional activity is a sensory component, since it involves the formation of a steady aspiration of the student to master the knowledge, skills and abilities and to acquire awareness of practical significance of social work.